The Invictus Games as a social component of adaptive sports - Dolbysheva , N.; Baldzhy , I.; Chukhlovina , V.; Buzoveria , A.; Cherniavska , O. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Adaptive sports in the international sports movement gained intensive development at the end of the 20th century. and the beginning of the 21st century. Its component includes the Paralympic, De-Olympic and Special Olympic movements. However, in 2014, at the initiative of Prince Harry and with the support of the Mayor of London Boris Johnson, the London Organizing Committee of the Olympic and Paralympic Games and the Ministry of Defense of England, the Invincible Games were founded. The main mission of the Games is to inspire the international community with the power of the invincible human spirit, to promote greater international understanding and respect for those who serve their country, to stimulate the recovery and support the rehabilitation of wounded and ill servicemen and veteran men and women from various countries. The Invincible Games are international sports competitions among servicemen and veterans who have been injured, wounded or ill during or as a result of their duty. The Invincible Games are designed to provide new opportunities for servicemen and veterans who have paid a high price for their devotion to their country and its people, as well as unite people and help them overcome the consequences of war wounds, injuries and illnesses with the support of family, friends and society. Purpose: to systematize historical and theoretical material on the organization and holding of international sports competitions of the Invincible Games among wounded servicemen and veterans as a social component of adaptive sports Research methods: analysis and generalization of scientific and methodical literature and Internet materials (oficial sites); historical analysis; scientific knowledge (analogies); system analysis. Result. The prerequisite for the organization and holding of the Invincible Games was the participation in 2013 of the British team of servicemen and veterans in the Warrior Games in adaptive sports. Prince Harry Albert David Mountbatten-Windsor (Duke of Sussex) visited and opened the Warrior Games in the USA. In 2014, Prince Harry founded, organized and held the first Invincible Games in London (England). From 2014 to 2023, six Invincible Games were held. In 2017, the national team of Ukraine participated for the first time in the III Games of the In-vincibles. In Ukraine, the Invincible Games Committee was established, whose mission is to support Ukrainian servicemen and veterans on the way to physical recovery, psychological rehabilitation and social integration, forming a positive outlook and motivating them to engage in sports and personal growth. From 2021, comprehensive competitions in adaptive sports, under the identity of the Invincible Games, the Warriors Cup within the framework of the Invincible League of Ukraine, will be organized and held. Conclusion. Historical and theoretical analysis of the system of organizing and conducting international competitions among wounded servicemen, defining their purpose, tasks, functions and principles of the system of training athletes of the Invincible Sports Movement and the Invincible Games allows us to state that they are a social component of adaptive sports.